UTILIZATION OF DIGITAL STORYTELLING TO ENHANCE NATIONALISM IN ELEMENTARY SCHOOL CHILDREN - Wahyu Ario Pratomo; Irsad; Sukma Hayati Hakim; Widya Sartika Hasibuan; Syarief Fauzie (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2023)
in the form of learning and training conducted by applying character values with real implementation through a storytelling approach and also utilizing digital technology in making learning schedules using Pop-up media to develop knowledge and creativity of elementary school children at Sekolah Indonesia Bangkok. Each learner received a digital storytelling-based learning briefing on cultural introduction as well as practicum materials in the form of creativity known as Pop-ups. The learning method used in this activity is Project Based Learning and participatory learning from students directly where students will get a basic understanding of understanding culture then students are also directed to carry out the practice of making pop-ups as an implementation of digital literacy that has been obtained. The results of learning and practice with pop-up media in elementary school children are very important to provide a fundamental understanding of students about culture and digital media-based learning practices in elementary school children.